The 1977 Election and Consolidation of the New Order Government in West Sumatra - Israr, Israr; Zuhdi, Susanto; Abdurakhman, Abdurakhman (Paramita: Historical Studies Journal, 2022)
This study aims to reveal the process and results of the 1977 Election in West Sumatra. Unlike at the national level taking place under intense competition, the second election during the New Order regime in West Sumatra seemed relatively “quiet.” Golkar comes out as the superior champion. The vote acquisition surpassed the Golkar votes nationally and passed the “Beringin” achievement in the 1971 Election. This study uses a structural history approach. The results show its specific dynamics in West Sumatra, which differed from the national elections. This study uses the historical method of heuristics, criticism, interpretation, and historiography. In the heuristic stage, data were obtained through library research, documentation and archives, field observations, and interviews with selected resource persons based on source criticism. The study results reveal that the 1977 Election in West Sumatra not only resulted in an increase in Golkar’s votes and the defeat of the “opposition party,” especially the PPP, but also signaled the continued consolidation of the New Order regime in Minangkabau. Penelitian ini bertujuan untuk mengungkap proses dan hasil Pemilu 1977 di Sumatera Barat. Berbeda dengan di tingkat nasional yang berlangsung dalam persaingan yang ketat, pemilu kedua pada masa Orde Baru di Sumatera Barat tampak relatif “tenang”. Golkar keluar sebagai juara unggul. Perolehan suara tersebut melampaui perolehan suara Golkar secara nasional dan melewati prestasi “Beringin” pada Pemilu 1971. Penelitian ini menggunakan pendekatan sejarah struktural. Hasil penelitian menunjukkan dinamika spesifik di Sumatera Barat yang berbeda dengan pemilu nasional. Penelitian ini menggunakan metode historis heuristik, kritik, interpretasi, dan historiografi. Pada tahap heuristik, data diperoleh melalui studi pustaka, dokumentasi dan arsip, observasi lapangan, dan wawancara dengan nara sumber terpilih berdasarkan kritik sumber. Hasil kajian mengungkapkan bahwa Pemilu 1977 di Sumatera Barat tidak hanya menghasilkan peningkatan perolehan suara Golkar dan kekalahan “partai oposisi” khususnya PPP, tetapi juga menandakan berlanjutnya konsolidasi rezim Orde Baru di Minangkabau. Cite this article: Israr, Zuhdi, S., Abdurakhman. (2022). The 1977 Election and Consolidation of the New Order Government in West Sumatra. Paramita: Historical Studies Journal, 32(2), 212-220. http://dx.doi.org/10.15294/paramita.v32i2.29705